The spatiality of emotion in early modern China : from dreamscapes to theatricality - Lam, Ling Hon (Columbia University Press, 2018)
"In this book, Lam reads sixteenth- to eighteenth-century Chinese drama through the dual lenses of theatricality and emotion. The book argues against both accounts of theatricality as a universal category and as an exclusively European phenomenon by historicizing the emergence of theatricality out of the medieval dreamscape in early modern China. In other words, this work clings tightly both to Western theory and to the necessity of reading texts in their own historical contexts. The book includes chapters on The Peony Pavilion, cross-gender performance, and cross-cultural exchanges. It both situates the Chinese culture of emotion in the global context and offers a new perspective on the historical formation of self and society in early modern China"--